Black Eagles and hyraxes - the two flagship species in the conservation of wildlife in the Matobo Hills, Zimbabwe - Chiweshe, Ngoni (Ostrich, 2007)
The Black Eagle (Aquila verreauxii) in the Matobo National Park is heavily dependent on two hyrax species, which form 98% of the diet. This raptor has been the subject of study in the Matobo Hills for the past 45 years. Its two main prey species, the Yellow-spotted Hyrax (Heterohyrax brucei) and the Rock Hyrax (Procavia capensis), have been under study for the past 13 years. There are three categories of land use in the Matobo Hills - national park, commercial farmland and communal land - and therefore varying levels of protection for the raptor and its prey. Local communities within the Matobo Hills depend on the hyrax as their main source of protein. This heavy utilisation has lead to population declines in both the prey (hyrax) and the raptor in some areas. In an effort to reverse or reduce this imbalance, since 1995 wildlife conservation education programmes have been introduced, focusing on 21 schools immediately surrounding the Matobo National Park. This educational programme is aimed at conserving not only the Black Eagle and hyraxes but the whole biodiversity of the hills.